1999
DOI: 10.1073/pnas.96.24.13691
|View full text |Cite
|
Sign up to set email alerts
|

Neural restrictive silencer factor recruits mSin3 and histone deacetylase complex to repress neuron-specific target genes

Abstract: Accumulative evidence suggests that more than 20 neuron-specific genes are regulated by a transcriptional cis-regulatory element known as the neural restrictive silencer (NRS). A trans-acting repressor that binds the NRS, NRSF [also designated RE1-silencing transcription factor (REST)] has been cloned, but the mechanism by which it represses transcription is unknown. Here we show evidence that NRSF represses transcription of its target genes by recruiting mSin3 and histone deacetylase. Transfection experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(198 citation statements)
references
References 61 publications
4
191
0
Order By: Relevance
“…REST binds the RE1 element of target genes and recruits CoREST (Andres et al, 1999;Ballas et al, 2001) and mSin3A (Naruse et al, 1999;Huang et al, 1999;Grimes et al, 2000;Roopra et al, 2001), corepressor platforms which in turn recruit HDACs-1 and 2. HDACs deacetylate core histone proteins and affect dynamic and reversible gene silencing (Roopra et al, 2001;Ooi and Wood, 2007).…”
Section: Transcriptional Regulation By Rest During Strokementioning
confidence: 99%
“…REST binds the RE1 element of target genes and recruits CoREST (Andres et al, 1999;Ballas et al, 2001) and mSin3A (Naruse et al, 1999;Huang et al, 1999;Grimes et al, 2000;Roopra et al, 2001), corepressor platforms which in turn recruit HDACs-1 and 2. HDACs deacetylate core histone proteins and affect dynamic and reversible gene silencing (Roopra et al, 2001;Ooi and Wood, 2007).…”
Section: Transcriptional Regulation By Rest During Strokementioning
confidence: 99%
“…The demethylating agents such as 5-aza-2'deoxycytidine (5-aza-CdR) and its homologues or valproic acid (VPA) are usually used for studying gene regulation [64] . Researches indicate that TSA can alleviate the transcription repression of the genes containing NRSE [61] . Hsieh et al [25] found that adult multipotent neural progenitor cells predominantly differentiated into neurons but not glia since glial differentiation was actively suppressed in the presence of VPA (Fig.2B).…”
Section: The Structure Of Mirna Researches Indicate That Mirnas Are Pmentioning
confidence: 99%
“…NRSE/NRSF can mediate transcriptional repression through associating with the mSin3A/B complex [61] , N-CoR [62] , and the novel co-repressor complex [55] CoREST/HDAC2 [63] . CoREST can recruit other silencing machinery to NRSF target genes, including the methyl-DNA binding protein MeCP2, heterochromatin protein 1, and histone lysine methyltransferase (the suppressor of variegation 39H1) [59] .…”
Section: Non-coding Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…REST is a powerful repressor. The N terminus of the molecule has the ability to recruit HDAC1/2 complexes and Sin3A, whereas its C terminus has the ability to form complexes with HDAC1/2 and with Co-REST (Andres et al 1999;Huang et al 1999;Naruse et al 1999;Roopra et al 2000). Accordingly, neuronal differentiation of embryonic or adult neural progenitors is initiated by the removal component of these large repressive complexes.…”
Section: Modulation Of Oligodendrocyte Lineage-specific Pathways By Hmentioning
confidence: 99%